2019
DOI: 10.1080/1828051x.2019.1589393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding less shell, extruded and enzymatically treated palm kernel cake on expression of growth-related genes in broiler chickens

Abstract: Boo & Zulkifli Idrus (2019) Effect of feeding less shell, extruded and enzymatically treated palm kernel cake on expression of growth-related genes in broiler chickens,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Endogenously produced SCFA and primarily butyrate was shown to increase insulin sensitivity and glycemic control in several in vivo studies with mammals [ 23 , 24 ]. Furthermore, Ramiah et al [ 47 ] found an increased mTOR mRNA level in the liver of broiler chickens, noting the high NSP level of the feed as a possible explanation. In our previous paper, we already reported lowered blood glucose levels of the animals used in this experiment in the WB group at the age of 3 weeks [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenously produced SCFA and primarily butyrate was shown to increase insulin sensitivity and glycemic control in several in vivo studies with mammals [ 23 , 24 ]. Furthermore, Ramiah et al [ 47 ] found an increased mTOR mRNA level in the liver of broiler chickens, noting the high NSP level of the feed as a possible explanation. In our previous paper, we already reported lowered blood glucose levels of the animals used in this experiment in the WB group at the age of 3 weeks [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, supplementation of low energy diets with an exogenous enzyme in broiler diets has promoted the absorption of the micronutrients via upregulation of GLUT-2 and Pep-T1 expressions [ 75 ]. Ramiah, et al [ 76 ] reported less shell PKC and enzyme-treated PKC feeding has upregulated the protein kinase C zeta (PRKCZ) gene expression, which plays an essential role in the insulin signalling pathway, and the mechanisms of glucose storage and uptake, protein synthesis and regulation of lipid synthesis. On the other hand, higher inclusion levels of oils in the PKC/LPKC diets have upregulated all transporters’ expressions compared to those with lower oil content ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the body weight gain was significantly lower for chickens fed with 10 and 15% PKC compared to the same levels of FPKC and control groups. Moreover, Rahim et al [ 69 ] using diets containing 25% PKC observed the growth performance of broilers fed with untreated and treated PKC groups was significantly ( p < 0.05) lower than the broilers fed the control (untreated) diet. These discrepancies of PKM and PKC findings may be due to the differences in oil extraction methods, which are solvent and expeller press that led variation in nutrient composition.…”
Section: Effects Of Pkc On Broiler Growth Performancementioning
confidence: 99%